Métodos de amostragem, influência dos fatores ambientais e guia de identificação dos escorpiões (Chelicerata, Scorpiones) da Reserva Ducke, Manaus, Amazonas, Brasil - Araújo, Juliana de Souza (Instituto Nacional de Pesquisas da Amazônia - INPA, 2007)
As ecological reserves are designed to encompass large geographical areas, the comprehension of the environmental functions must be done through studies that represent the patterns of the area to be preserved. The objectives of this study were: 1) to evaluate the efficiency and the cost-benefit of two sampling methods: the active sampling, using ultraviolet light (UV) and the passive sampling, using large and small pitfall traps, 2) to establish alternative protocols for sampling scorpions, 3) to evaluate the distribution pattern of the species in relation to the percentage of sand in the soil, inclination, depth of litter, the number of fallen trunks, and of palm trees, and 4) to elaborate an identification guide for the species registered for the reserve, to facilitate the work of the non-specialists. Sampling was carried out along a grid of trails traversing 35 km2 of rainforest in the Reserva Ducke, Manaus. Thirty-eight 250 m transects representative of the local diversity of soils and topography were sampled during the season of lower rainfall 2005/2006. Five of the eight species of scorpions recorded from the reservation were collected, representing 63% of the total already registered in the reserve. The species were: Ananteris dekeyseri Lourenço, 1 982; A. pydanieli Lourenço, 1 982; Tityus metuendus Pocock, 1897; Brotheas amazonicus Lourenço, 1988, and Chactopsis amazonica Lourenço & Francke, 1986. The 3 species not collected during thisstudy have very specific habitat in the reserve. The species A. dekeyseri, A. pydanieli e C. amazonica, considered to be ground-dwelling,' were sampled exclusively in the pitfall traps. B. amazonicus was the most abundant species and present in all of the plots, and was registered by both methods and by the two sizes of pitfall traps. T. metuendus, a tree-living species, was sampled mainly through active sampling. The results indicate that the active sampling is more indicated to sample arboricolous species, and can be used during the day or night, and the passive method (pitfall traps) is the most appropriate for soil species. The results obtained through the use of the two different sizes of pitfall traps were similar in relation to the abundance of the sampled species: We suggest that the large pitfall traps may be used for joint inventories together with other taxa (reptiles, amphibians and small mammals), and during long sample periods, because of the large impact to the environment and the high costs. We are indicating the small pitfall traps for sampling scorpions and other soil invertebrates because of the easiest manipulation, lowest costs and lowest environmental impact. For a complete inventory of the scorpion fauna, we are suggesting the utilization of both methods, as each of them sampled all of the species registered in our study. The environmental variables utilized did' 'not explain the distribution pattern of the majority of the species, but the sandy percentage in the soil had influence in the presence of A. dekeyseri. We suppose that this relation is indirect, because the variable is related to the proximity of water bodies and it is possibly that the distribution of this species is associated to this factor. This species is rare, and more studies are necessary to understand how the environmental factors may influence its distribution. A guide consisting of a simplified pictorial key and diagnosis of each species know from the Reserva Ducke is presented.
Keywords: Comunidade de escorpiões; Chelicerata, Scorpiones